Variation in Carbon Fixation and Water Use Efficiency Among Date Palm Cultivars Grown in Arid Zone (Indian Journal of Arid Horticulture, 2025)
Seven commercial cultivars of date palm (Halawy, Khadrawy, Shamran, Zahidi, Medjool, Khuneizi and Khalas) were evaluated on the basis of physiological parameters. The net photosynthetic rate, transpiration, stomatal conductance and internal CO, concentration were estimated using LI-6200 Infra Red Gas Analyzer. The values of carboxylation efficiency and water use efficiency were computed. The results demonstrate that in date palm maximum rate of photosynthesis occurs during spathe emergence stage, which shows that probably this stage has a high sink demand. It was further noticed that higher rate of photosynthesis in date palm is on account of higher stomatal conductance. Inter-cultivars comparison revealed that cv. Halawy might have advantage over others in hot arid ecosystem, as this cultivar possesses high rate of photosynthesis, water use efficiency and carboxylation efficiency.
Keywords: Arid ecosystem; date palm; carboxylation efficiency; photosynthesis